DETERMINING ARCHITECTURAL COMPOSITION THROUGH INFRASTRUCTURAL TENETS - Kordić, Nemanja (Arhitektura i urbanizam, 2021)
Today, in the 21st century within the context of the neo-liberal market, architecture has become a tool of capital, demanding minimal investment with maximum spatial and environmental performance. Permanent changes that follow the rapid development of an information-based society imply an infrastructural take on the architectural composition, which has become increasingly programmatically unstable and market driven. Therefore today, an architectural composition traditionally understood as a set of part to-whole relations on three basic levels: form, function (program and its performance) and structure, can be perceived through the relations between volume, program range and infrastructure (which integrates the structural and performative aspects).Beginning with the hypothesis that socio-economic changes alter the conceptions of infrastructure in the design process, and understanding ways to transform the architectural composition, a set of key historical moments and relations are established between the development of: architectural tools and methodologies, norms and policies of spatial and energy efficiencies, and understanding infrastructure as an omnipresent element within the architectural composition. In urban design and architectural design, two terms can be distinguished: infrastructural ground – a term that brings infrastructure closer to the architecture scale, and infrastructural tenets, which are methods in the design process used to evaluate the spatial efficiency and the capacities for programmatic change, determining the relation between transformations within the design process and those of a completed project. Therefore, a new design approach is needed to define the capacities of programmatic transformations that can follow different models: flexibility, performativity and process, while maintaining the optimal spatial efficiency.The research showed that the choice of a transformational strategy depends on the program and envelope typologies to determine a project-specific infrastructural tenet – the layout of infrastructural elements which is located and quantified using the basic spatial efficiency parameters and indicators. As a launching point for further research, a theoretical matrix is proposed for four envelope typologies and three dominant program typologies, followed by a list of basic spatial efficiency parameters to loosely describe their infrastructural layouts.
Keywords: infrastructure; infrastructural tenet; architectural composition; spatial efficiency; infrastructural ground